The role of oligosaccharide in transport of egg yolk riboflavin-binding protein to the egg - Miller, Mark S.; Buss, Edward G.; Clagett, Carlo O. (Biochimica et biophysica acta, 1981)
The carbohydrate portion of chicken egg yolk riboflavin-binding protein was examined to determine its role in the biological activity of the protein. Yolk RBP was found to contain 5–6 mannose, five galactose, 12 N-acetylglucosamine and four sialic acid residues. Specific modifications of the oligosaccharide moiety were performed which included removal of sialic acid by mild acid hydrolysis, oxidation of galactose oxidase, and removal of N-acetylglucosamine and galactose residues by a mixture of glycosidases from Aspergillus niger. All of the modified proteins retained the ability to bind riboflavin although their capacities were lower than that of native yolk RBP. Circular dichroism of the modified yolk RBP samples showed changes in the near ultraviolet, but molar ellipticities in the far ultraviolet displayed only minor variations indicating no gross structural changes. All samples cross-reacted with RBP-specific antiserum. The plasma half-life of 125I-labeled yolk RBP was 62 min. Each of the modified samples was cleared more rapidly from the blood than native yolk RBP. Removal of sialic acid decreased the half-life of yolk RBP by 31%, while the other modifications decreased the half-life by as much as 60%. During a 10-day period following injection of 125I-labeled yolk RBP, 5.9% of the labeled protein was recovered from egg yolk. Relative to native yolk RBP, the transport of asialo-yolk RBP was decreased by 82%. The other modifications resulted in even less transport to the egg, the lowest being glycosidase-treated asialo-yolk RBP which was decreased by over 99%. By comparison of samples with similar clearance times, a positive correlation was made between sialic acid and ovarian transport.